Fermentation of coconut milk into virgin coconut oil using yeast for biodiesel production - Abdul Rahman, Arslin Rasyiqah; Samidin, Salma; Lahuri, Azizul Hakim; Dzakaria, Norliza (Malaysian Institute of Chemistry, 2024)
Virgin coconut oil (VCO) widely used in food industries, pharmaceuticals as well as beauty industries. Currently, the source of fossil fuels is facing extinction and is predicted to last for only another 50 years. Biodiesel produced by VCO has been indicated to be the perfect substitute for diesel. However, the methods for producing VCO such as heating cost a lot money, energy and time. The fermentation method has been shown to be the most convenient method for producing VCO. This research aims to find the best method for producing VCO for biodiesel production. Specifically, this research aims to determine the yield of VCO produced by the fermentation technique using four types of yeast namely bread yeast, tapai yeast, tempeh yeast and bread yeast with the addition of pineapple extract at different times of fermentation. The result of the organoleptic test, free fatty acids (FFA) test, and iodine test were compared, and VCO was then converted into biodiesel by transesterification using different amounts of catalyst to calculate its percentage yield. The results show that the highest yield percentage of VCO is 28.1% via the fermentation of tapai yeast for 18 hours with an FFA value of 0.8%. For biodiesel production, the transesterification of VCO produced using tapai yeast with 0.3 wt% potassium hydroxide (KOH) showed the highest yield percentage at 7 minutes (81.9%). In conclusion, the fermentation of coconut milk using 0.2 g of tapai yeast at 18 hours is the best method for producing VCO. Additionally, transesterification using 0.3 wt% KOH at 7 minutes is the best condition for biodiesel conversion.